The Effect of Intellectual Capital on The Performance of Islamic Banks Based on The Islamicity Performance Index (Case Study of Sharia Commercial Banks for the Period 2014-2018) - Annio Indah Lestari Nst; Dinda Abdita Siregar; Taufiq Taufiq (Journal of Management and Business Innovations, 2020)
This study aims to determine the effect of intellectual capital (IC) on the performance of Islamic bank in Indonesia. The independent variable is the intellectual capital which is measured using the Value Added Intellectual Coefficient (VAIC) with three main components namely VACA, VAHU, and STVA. The dependent variable is the performance of Islamic banks measured by the Islamic approach or Islamicity Performance Index through Zakat Performance Ratio (ZPR). The sample is Islamic Commercial Bank (BUS) in Indonesia which is registered in the Financial Services Authority (OJK) period of 2014-2018. The sample was selected by using purposive sampling method and obtained seven Islamic Commercial Banks. The results of this research shows that intellectual capital (IC) has no effect on the performance of Islamic banks based on the Islamic approach or the Islamicity Performance Index, especially on the ZPR of Islamic banks both partially and simultaneously.Keywords: Intellectual capital, Islamicity performance iIndex, ZPR